Response, Emotional Impact and Expectation of Family Caregiver in Caring For Family Member with Covid-19: A Qualitative Study - Widya Naralia; Henny Permatasari (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: The increasing number of COVID-19 cases has led to the collapse of health facilities so that treatment is not only carried out at the hospital, but also at home by involving the family. The rapid spread, rapid deterioration of health status and the uncertain treatment have caused fear for Covid-19 patients and also for those around them. Family caregivers are the closest people who responsible to provide care the Covid-19 patients at home. Various experiences of family caregivers provide an overview of the emotional response and impact as well as expectations while caring for family members with Covid-19. The purpose of this study was to obtain meaning and significance from family experiences in caring for family members who were confirmed to be COVID-19. Methods: The method used is qualitative with a descriptive phenomenological approach with data collection through in-depth interviews. There are 14 participants who are families who take care of family members with COVID-19 at homes in the North Sumatra. Data analysis was performed using the Colaizzi technique. Results: The results of this study discuss 2 main themes, namely the theme of response and emotional impact, and the expectations of family caregivers while providing care. Conclusion: family caregivers reveal negative emotional responses and emotional impacts, psychological and social changes from family caregivers. Family caregivers also expressed hope for assistance from the government and the community around their life. Conclusion: The results of this study provide a real picture of how the feelings and expectations felt by the family caregivers of Covid-19 patients.